Mechanism analysis of the abnormal head-cover vibration of an ultra-high-head pump-turbine operating in pump mode by CFD and FEM - Song Xue; Haolin Tian; Yongguang Cheng; Xiaoxia Hou; Ziwu Guan; Weijia Yang; Zhiyuan Wang; Zhaoning Wang; Qiyuan He (Engineering Applications of Computational Fluid Mechanics)
Hydraulic excitation causes abnormal head-cover vibration in some pump-turbines, particularly as design heads continue to rise. Pump-turbines with heads exceeding 600 m have reported such vibrations in pump mode, and it is urgent to reveal the reasons. A study was conducted on a head-cover of a pump-turbine with a maximum head of 660 m by 3D computational fluid dynamics (CFD) and finite element method (FEM) numerical simulations to investigate the hydraulic excitation source and vibration mechanism. Results show that the intensive vibration is related to the coincidence of frequency and mode between abnormal pressure pulsations with frequency 6–8fn and the low-order wet mode of the head-cover. A new flow pattern termed the rolling vortex was discovered in the vaneless space under high-head pumping conditions. The 6–8fn pressure pulsations result from the interaction between rolling vortices and guide-vanes, similar to the rotor-stator interaction. The flow mechanism of the rolling vortices is that the outflow velocity near the hub at the runner outlet is higher than that near the shroud, due to the positive blade lean angle and the X-shape distorted blades. Suppressing rolling vortices may help eliminate the abnormal head-cover vibration, which will be attempted in further study.